2009
DOI: 10.1152/japplphysiol.91232.2008
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reverses age-related decrements in endothelium-dependent dilation in skeletal muscle feed arteries

Abstract: We tested two hypotheses, first that exercise training reverses age-related decrements in endothelium-dependent dilation in soleus muscle feed arteries and second that this improved endothelium-dependent dilation is the result of increased nitric oxide (NO) bioavailability due to increased content and phosphorylation of endothelial NO synthase (eNOS) and/or increased antioxidant enzyme content. Young (2 mo) and old (22 mo) male Fischer 344 rats were exercise trained (Ex) or remained sedentary (Sed) for 10-12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 56 publications
6
72
0
1
Order By: Relevance
“…Apart from superoxide production, oxidative stress also can be regulated by antioxidant enzymes. SODs are enzymes that scavenge superoxide to form hydrogen peroxide and play a role in preserving NO bioavailability in the vasculature (32,47). In our study, db/db mice showed decreased endothelial function compared with Con, but TEMPOL incubation partially restored endothelial function in db/db, suggesting an increase of antioxidant enzymes may contribute to restoring endothelial function (Fig.…”
Section: Role Of Et In Endothelial Function Independent Of the Changementioning
confidence: 58%
See 1 more Smart Citation
“…Apart from superoxide production, oxidative stress also can be regulated by antioxidant enzymes. SODs are enzymes that scavenge superoxide to form hydrogen peroxide and play a role in preserving NO bioavailability in the vasculature (32,47). In our study, db/db mice showed decreased endothelial function compared with Con, but TEMPOL incubation partially restored endothelial function in db/db, suggesting an increase of antioxidant enzymes may contribute to restoring endothelial function (Fig.…”
Section: Role Of Et In Endothelial Function Independent Of the Changementioning
confidence: 58%
“…Previous studies indicated that reactive oxygen species (ROS) such as superoxide (O 2 ·Ϫ ) readily react with NO to form peroxynitrate (ONOO Ϫ ), which results in decreased NO bioavailability (8,10,32,47). Oxidative stress is tightly regulated by a balance between production and removal facilitated by enzymatic activity in the healthy condition, whereas cell damage induced by excessive oxidative stress can contribute to diabetes-induced atherosclerosis and coronary artery disease (8, 9).…”
mentioning
confidence: 99%
“…Differences in SOD-1, catalase, and glutathione peroxidase-1 (GPx-1) protein content in soleus muscle feed arteries were assessed by immunoblot analysis. Feed arteries were used in these analyses due to limitations of tissue volume in soleus muscle 1A arteriolar samples; however, aging-and training-induced adaptations of feed arteries generally parallel those of 1A arterioles (59,66). Vessels were isolated, snap frozen, and stored at Ϫ80°C.…”
Section: Evaluation Of Oonomentioning
confidence: 99%
“…Exercise or physical activity may contribute to improvement of insulin resistance via improved insulin action, improved vascular function via increase of nitric oxide (NO) bioavailability, and by increasing ROS-detoxification and decreasing ROS generation [48][49][50][51][52][53] . Since generation of ROS is a normal result of aerobic metabolism, it is efficiently removed by cellular anti-oxidant systems under physiological conditions.…”
Section: Role Of Exercise and Physical Activity In Antioxidant Processesmentioning
confidence: 99%